Estudo randomizado testando musicoterapia na redução da fadiga relacionada ao câncer em mulheres com neoplasia maligna de mama ou ginecológica em curso de radioterapia - Alcântara-Silva, Tereza Raquel de Melo (2012)
To study the influence of music therapy in reduction of Fatigue related to cancer in patients with breast’s or gynecology’s cancer, during the radiotherapy treatment. METHODS: This is a randomized controled study (Control Group - CG e Musictherapy Group - MTG) wich values fatigue, life’s quality, anxienty, depression by using evaluative instruments Functional Assessment of Cancer Therapy: Fatigue (FACT-F), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) in three differents moments (during first week of radiotherapy, in the intermediate phase’s week and during the last week of radiotherapy) for patients of bouth groups. Women allocated in MTG, in addition to the scales described above, answered the Music therapy Questionary (MQ), and the Subjective Impression of the Subject’s Questionary in last meeting. Music Therapy sessions were individual and lasted an average of 40 minutes. Music therapeutic techniques used were Musical Audition (MA) and Therapeutic Musical Audition (TMA). RESULTS: 164 women were randomized and 116 women with middle age of 52,9 (CG) and 51,85 years (MTG) were included in the analysis. MTG’s patients had on average 10 music therapy sessions, totalizing 509 assistences during the search. In the analysis between groups, Functional Assesment of Cancer Therapy: Fatigue (FACIT-F) demonstrated significance related to Trial Outcome Index (TOI) (p=0,011), Functional Assesment of Cancer Therapy – Geral (FACT-G) FACT-G (p=0,001) FACIT-F FACT-F(p=0,005) areas to the MGT compared to CG. In comparisson made inside the same group results pointed a significant worsening for women. The GMT showed a significant in TOI, FACT-G and FACIT – F (p<0,001) areas in fatigue scale. Music Therapy Questionary showed that 59,3% of the pacients didn’t know what music therapy was, and 53,7% thought that Music Therapy was a relaxing activity. In the end of the process, based on ISS, 98,1% of the women afirmated that Music Therapy made difference in their lives, 96,2% reported a positive perception of music therapy, 75,5% noticed less fatigue and 84,9% reported less stress. CONCLUSION: Individual Music therapy is effective in treatment of Fatigue Related to Cancer during the radiotherapy, to depression and to improve quality of life.